Die funksie van die "danksegging(s)" in 1 Tessalonisense - Cornelius, E. (Hervormde teologiese studies, 1993)
The function of the ‘thanksgiving(s)’ in 1 Thessalonians The aim of this article is to determine the possible communicative function(s) of the 'thanksgiving (s)’ in 1 Thessalonians. Traditionally more than one ‘thanksgiving’ is identified in this letter (contrasting the other Pauline letters containing only one ‘thanksgiving’). Approaches like the formalist and /or ‘content’ approaches are rendered as inadequate to deal with this problem. The interactive model seems to be a more satisfactory approach to determine the function(s) of these sections in 1 Thessalonians. This approach leads to the conclusion that ‘thanksgiving’ is a misnomer for these sections in 1 Thessalonians; their function is rather to render the implied reader favourable towards the encoded author so that he/she can be receptive to his argumentation.